2017
DOI: 10.1186/s12864-017-4357-3
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Sertoli cell-specific transcripts in the mouse testis and the role of FSH and androgen in the control of Sertoli cell activity

Abstract: BackgroundThe Sertoli cells act to induce testis differentiation and subsequent development in fetal and post-natal life which makes them key to an understanding of testis biology. As a major step towards characterisation of factors involved in Sertoli cell function we have identified Sertoli cell-specific transcripts in the mouse testis and have used the data to identify Sertoli cell-specific transcripts altered in mice lacking follicle-stimulating hormone receptors (FSHRKO) and/or androgen receptors (AR) in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 68 publications
0
35
0
Order By: Relevance
“…This raises the possibility that testicular endothelial cells and fibroblasts might also express WT1 and FSHr. In addition, Soffientini et al (2017) showed that the ablation of Sertoli cells does not extinguish Wt1 transcripts in the testis, confirming that some of the markers currently accepted as Sertoli cell-specific are also expressed by other testicular cells types (Soffientini et al, 2017); thus limiting their use to characterize Sertoli cells.…”
Section: Markers Used To Evaluate the Purity Of Rodent Sertoli Cellmentioning
confidence: 93%
See 1 more Smart Citation
“…This raises the possibility that testicular endothelial cells and fibroblasts might also express WT1 and FSHr. In addition, Soffientini et al (2017) showed that the ablation of Sertoli cells does not extinguish Wt1 transcripts in the testis, confirming that some of the markers currently accepted as Sertoli cell-specific are also expressed by other testicular cells types (Soffientini et al, 2017); thus limiting their use to characterize Sertoli cells.…”
Section: Markers Used To Evaluate the Purity Of Rodent Sertoli Cellmentioning
confidence: 93%
“…Sertoli cells exhibited some enriched transcripts with high levels of expression between birth and PND 6, and others rising at PND 8, peaking between PND 10 and 14, and returning to basal levels after 14-18 days (Shima et al, 2004). In fact, none of the Sertoli-specific transcripts were present in a steady-state over time, Although a number of studies were performed to identify new Sertoli cell markers, there is little agreement between the findings (De Gendt, Verhoeven, Amieux, & Wilkinson, 2014;Green et al, 2018;Sanz et al, 2013;Soffientini et al, 2017;Zimmermann et al, 2015). Interestingly, from hundreds of identified transcripts, only 42 (5-12%) appeared consistently in all these studies (Table 2), and some of the transcripts considered specific for Sertoli cells by the authors, such as Amh, Sox9, Rhox5, and Gdnf, were excluded from the selection.…”
Section: Markers Used To Evaluate the Purity Of Rodent Sertoli Cellmentioning
confidence: 99%
“…Results showed a differentiation process from mESCs to eSLCs was established mimetic to the presumptive developmental process in embryos. Furthermore, the induced eSLCs had similar characteristic and expression of specific markers with eSCs including, AMH + , FSHR + , GDNF + , FASL + , and EMX2 − [1,41,42]. Moreover, through the inducing approach, there were ring-like structures and tubular-like structures formed as the same behavior as those eSCs in embryos [6,43].…”
Section: Introductionmentioning
confidence: 72%
“…The general phenomenon is that FSH mostly elevates the expression of a large number of Sertoli cell genes (5557). In neonatal life, Sertoli cells proliferate extensively, and logically mainly the transcripts of genes involved in DNA replication, cell cycle and stem cell factors are enriched (54).…”
Section: Fsh Regulates Genes Involved In Proliferation Structure Anmentioning
confidence: 99%
“…FSH also regulates the expression of genes involved in fatty acid metabolism and mitochondrial biogenesis, which is vital for the energy metabolism of seminiferous tubules (71). Another example of FSH-induced actions of Sertoli cells on germ cells is Aqp8 , one of the most altered genes in the absence of FSH action (57). Aqp8 is involved in water transport through membranes (72) and is strongly down-regulated in Fshr -KO mice (57).…”
Section: Fsh Regulates Genes Involved In Proliferation Structure Anmentioning
confidence: 99%